University–Industry Collaboration in Turkish SMEs: Investigation of a U-Shaped Relationship. (May 2013) - Temel, Serdal; Scholten, Victor; Akdeniz, R. Cengiz; Fortuin, Frances; Omta, Onno
University–industry collaboration and innovation are popular topics in emerging countries. Although the main premise is that such collaboration and innovation increase firm performance, the empirical evidence is inconclusive. Drawing on a sample of 79 Turkish small and medium-sized enterprises (SMEs), the authors find negative direct effects of innovation-based strategy and university collaboration on the profit growth of firms. However, where there is fierce market competition, they find that an innovation-based strategy increases profit growth and that collaboration with universities needs to exceed a certain level before the benefits are manifested in profit growth. These results contribute to the debate on the role of innovation and university collaboration in the profit growth of SMEs in emerging countries. For managers, the implications are that an innovation-based strategy is important in competitive markets in emerging countries, and that university collaboration needs to be taken more seriously and must involve higher levels of effort and commitment if benefits are to emerge; otherwise, companies may decide against working with universities.